Pengaruh Media Berbasis Game Kahoot Terhadap Pemahaman Siswa Kelas X-2 Pada Mata Pelajaran Al-Qur'an Hadis Di MSA Nusantara Bungah Gresik - Ahmad Mughni Labib Al Ikhwani; Alimin; Muttaqin Khabibullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2026)
The teaching of Al-Qur’an and Hadith at the senior high school level continues to face various challenges, particularly students’ low understanding of the subject matter. Preliminary observations in Class X-2 of SMA Nusantara Bungah revealed that many students had not achieved the Minimum Mastery Criteria (MMC), while the learning process was still dominated by lecture-based instruction, which tended to be monotonous. Therefore, a more innovative and interactive learning medium is needed to improve students’ understanding. This study aimed to determine students’ level of understanding before the use of Kahoot-based game learning media, describe the implementation process of Kahoot in Al-Qur’an and Hadith learning, and examine students’ level of understanding after using the media. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 22 students from Class X-2 selected through total sampling. Data were collected through observation, tests, questionnaires, and documentation. The research instruments were developed based on learning media indicators and comprehension indicators derived from Bloom’s Taxonomy. The results showed that before the implementation of Kahoot, most students demonstrated low to moderate levels of understanding, with average scores remaining below the MMC. Kahoot was implemented through game-based quizzes supported by digital devices. During the learning process, students appeared more active, enthusiastic, and engaged. After the use of Kahoot, students’ understanding improved, as indicated by higher posttest scores and an increased number of students achieving the MMC. These findings suggest that Kahoot is an effective learning medium for improving students’ understanding in Al-Qur’an and Hadith subjects.